Investigation of performance characteristics of plastic pyrolysis oil and crude palm oil fuel on diesel engine - Jaat, Norrizam; Azizul, Muhamad Asri; Khalid, Amir; Ahmad Jais, Mohamad Harizat; Zainal Abidin, Shaiful Fadzil; Mustaffa, Norrizal; Ishak, Izuan Amin; Manshoor, Bukhari; Didane, Djamal Hissein; Zahari, Izzarief (Seventh Sense Research Group, 2021)
Nowadays, with the increment of fossil fuel engines, there have been facing the downside of a fuel problem, and the survival of those engines has been vulnerable. The dependency on a single source which is a fossil fuel is a worrying issue because the fossil fuel is limited and takes millions of years to produce. In this paper, the performance of the alternative fuels on a diesel engine is analyzed and compared with the standard diesel to determine its compatibility with the diesel engine without any modification. The research study of the performance of plastic pyrolysis oil and crude palm oil blended with diesel at a different concentration which is 20% and 25%, on automotive 4 stroke diesel engine test system were illustrated in this paper. The brake power engine, thermal brake efficiency, brake specific fuel consumption, and exhaust temperature of the blended fuels are recorded and analyzed. The value of brake-specific consumption decreases as the concentration of the pyrolysis oil increases while thermal brake efficiency is increased. The blended fuels recorded lower brake thermal efficiency, brake-specific fuel consumption, and higher exhaust gas temperature compared to standard diesel fuel. In the aspect of performance of the diesel engine, the uses of crude palm oil and plastic pyrolysis oil are usable and applicable.